Poly(3-hydroxybutyrate) hyperproduction by a global nitrogen regulator NtrB mutant strain of Paracoccus denitrificans PD1222. Issue 1 (6th December 2017) - Olaya-Abril, Alfonso; Luque-Almagro, Víctor M; Manso, Isabel; Gates, Andrew J; Moreno-Vivián, Conrado; Richardson, David J; Roldán, María Dolores
Abstract: Paracoccus denitrificans PD1222 accumulates short-length polyhydroxyalkanoates, poly(3-hydroxybutyrate), under nitrogen-deficient conditions. Polyhydroxybutyrate metabolism requires the 3-ketoacyl-CoA thiolase PhaA, the acetoacetyl-CoA dehydrogenase/reductase PhaB and the synthase PhaC for polymerization. Additionally, P. denitrificans PD1222 grows aerobically with nitrate as sole nitrogen source. Nitrate assimilation is controlled negatively by ammonium through the two-component NtrBC system. NtrB is a sensor kinase that autophosphorylates a histidine residue under low-nitrogen concentrations and, in turn, transfers a phosphoryl group to an aspartate residue of the response regulator NtrC protein, which acts as a transcriptional activator of the P. denitrificans PD1222 nasABGHC genes. The P. denitrificans PD1222 NtrB mutant was unable to use nitrate efficiently as nitrogen source when compared to the wild-type strain, and it also overproduced poly(3-hydroxybutyrate). Acetyl-CoA concentration in the P. denitrificans PD1222 NtrB mutant strain was higher than in the wild-type strain. The expression of the phaC gene was also increased in the NtrB mutant when compared to the wild-type strain. These results suggest that accumulation of poly(3-hydroxybutyrate) in the NtrB mutant strain of PD1222 responds to the high levels of acetyl-CoA that accumulate in the cytoplasm as consequence of its inability to efficiently use nitrate as nitrogen source. Abstract : Overproduction of short-length polyhydroxyalkanoates by the P. denitrificans NtrB mutant grown with nitrate has been shown by fluorescence and transmission electron microscopy. This hyperaccumulation of polyhydroxyalkanoates has been associated with increased phaC gene expression, determined by qRT-PCR, and an elevated intracellular accumulation of acetyl-CoA measured by fluorescence.